Tyrosine phosphorylation within the SH3 domain regulates CAS subcellular localization, cell migration, and invasiveness - Janoštiak, Radoslav (The American Society for Cell Biology, 2011)
Crk-associated substrate (CAS) is a major tyrosine-phosphorylated protein in cells transformed by v-crk and v-src oncogenes and plays an important role in invasiveness of Src-transformed cells. A novel phosphorylation site on CAS, Tyr-12 (Y12) within the ligand-binding hydrophobic pocket of the CAS SH3 domain, was identified and found to be enriched in Src-transformed cells and invasive human carcinoma cells. To study the biological significance of CAS Y12 phosphorylation, phosphomimicking Y12E and nonphosphorylatable Y12F mutants of CAS were studied. The phosphomimicking mutation decreased interaction of the CAS SH3 domain with focal adhesion kinase (FAK) and PTP-PEST and reduced tyrosine phosphorylation of FAK. Live-cell imaging showed that green fluorescent protein–tagged CAS Y12E mutant is, in contrast to wild-type or Y12F CAS, excluded from focal adhesions but retains its localization to podosome-type adhesions. Expression of CAS-Y12F in cas–/– mouse embryonic fibroblasts resulted in hyperphosphorylation of the CAS substrate domain, and this was associated with slower turnover of focal adhesions and decreased cell migration. Moreover, expression of CAS Y12F in Src-transformed cells greatly decreased invasiveness when compared to wild-type CAS expression. These findings reveal an important role of CAS Y12 phosphorylation in the regulation of focal adhesion assembly, cell migration, and invasiveness of Src-transformed cells.